Financial Liquidity as a Leading Criterion for Evaluating an Enterprise - Babuśka, Ewa Wiktoria (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article discusses financial liquidity considered as a leading indicator of company performance. Financial liquidity is a function of shaping the proper relationship of receipts to expenditure in the management process. Its essence, methods of determination and analysis are presented on the basis of the balance sheet and cash flow statement, showing liquidity ratios, their classification and interpretation. The survey of financial liquidity in Polish companies was based on the example of unit financial statements of PKN Orlen SA. for the years 2013–2016. Cash flow and static and dynamic liquidity ratios were analysed. Research methods include a review of the literature on reporting, liquidity and financial analysis, interpretation of related legislation, analysis of financial statements, and inference. The results confirm that liquidity, which ensures a company’s balance and stability, is today the most important parameter in assessing a company.